(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
I.S. Ivchenko. Development of dendrology in the XVIII-XX centuries. - K.: NPU im. M.P. Dragomanova, 2009. - 287 p. I.S. Ivchenko. Historical form of dendrology. K.: Type of NPU named after M.P. Dragomanova, 20011. - 351 p.